(untitled) (AYUSHDHARA, 2025)
Gouty arthritis is a form of inflammatory arthritis characterized by sudden and severe pain, redness, and swelling in the joints. It happens when too much uric acid builds up in the blood, forming sharp crystals in and around joints. These crystals usually affect the big toe, ankles, knees, wrists, and elbows. In Ayurveda, gouty arthritis closely resembles a disorder called Vatarakta in which the Vata dosha becomes aggravated and combines with vitiated Rakta, leading to disturbances in the joints and surrounding tissues. A 24-year-old male patient presented to the OPD with chief complaints of acute pain and swelling in the right ankle joint for the past 6 months, along with elevated serum uric acid levels. He was treated with Panchakarma therapy, including Udwartana, Parisheka, and Kokilaksha Kashaya Niruha Basti for 14 days. These therapies have shown significant effectiveness in reducing joint pain and swelling, as well as lowering serum uric acid levels. By addressing both the symptoms and the underlying causes, these Ayurvedic treatments offer a holistic approach to managing gout. Their combined action not only alleviates discomfort but also promotes long-term relief, making them valuable interventions in the effective treatment of gout.